Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

A inequality proposed at Zhautykov Olympiad 2008

Let be $a,b,c >0$ with $abc=1$. Prove that:

$$\sum_{cyc}{\frac{1}{(a+b)b}} \geq \frac{3}{2}.$$

$a=\frac{x}{y}$, $b=\frac{y}{z}$, $c=\frac{z}{x}$.

Our inequality becomes: $$\sum_{cyc}{\frac{z^2}{zx+y^2}} \geq \frac{3}{2}.$$ Now we use that: $z^2+x^2 \geq 2zx.$ $$\sum_{cyc}{\frac{z^2}{zx+y^2}} \geq \sum_{cyc}{\frac{2z^2}{z^2+x^2+2y^2}} \geq \frac{3}{2}.$$

Now applying Cauchy Schwarz we obtain the desired result .

What I wrote can be found on this link: mateforum. But now, I don't know how to apply Cauchy-Schwarz .


share|cite|improve this question
What is the notation $\sum_{cyc}$? – Willie Wong Sep 25 '12 at 9:19
Tell me if this is where you get stuck: If $S$ is the last sum you have above, then using Cauchy-Schwarz you can obtain the inequality $$\tfrac{1}{2}S(4x^2 + 4y^2 + 4z^2) \ge (x + y + z)^2.$$ What's disturbing about this is that you then get $S \ge \tfrac{1}{2} (x + y + z)^2/(x^2 + y^2 + z^2)$. It would be natural then to try to prove that $(x + y + z)^2 / (x^2 + y^2 + z^2) \ge 3$, but instead the reverse is true; $(x + y + z)^2 / (x^2 + y^2 + z^2) \le 3$. – Christopher A. Wong Sep 25 '12 at 9:25
@daniel, the summation is cyclic, so the full summation is $$\frac{1}{(a+b)b} +\frac{1}{(b+c)c} + \frac{1}{(a+c)a}$$. – Christopher A. Wong Sep 25 '12 at 10:04
Oh thanks. Will delete my comment. – daniel Sep 25 '12 at 20:35
up vote 2 down vote accepted

Since $\mathrm{LHS}$ of last inequality is homogeneous we can assume $x^2 + y^2 + z^2 = 1$. Then it becomes $$ \mathrm{LHS} = 2\sum_{cyc} \frac {x^2} {1 + z^2} =:2I $$ Now using Cauchy-Schwarz inequality we get $$ 1 = (x^2 + y^2 + z^2)^2 = \left(\sum_{cyc} x\sqrt{1 + z^2} \cdot \frac x {\sqrt{1 + z^2}}\right)^2 \leq\\ \left(\sum_{cyc} x^2(1 + z^2)\right) \cdot \left( \sum_{cyc} \frac {x^2}{1 + z^2} \right) = I \cdot \sum_{cyc} x^2(1 + z^2) $$ To finish, let's note that CS inequality implies $$ x^2\cdot z^2 + y^2 \cdot x^2 + z^2 \cdot y^2 \leq x^4 + y^4 + z^4 $$ and therefore $$ \sum_{cyc} x^2(1 + z^2) = 1 + x^2 z^2 + y^2 x^2 + z^2 y^2 \leq 1 + \frac {(x^2 + y^2 + z^2)^2} 3 = \frac 4 3 $$

share|cite|improve this answer
I have a question :) How do you know to apply the relation of homogenity and how do you apply it ? Why $x^2+y^2+z^2=1? $ Thanks :) – Iuli Sep 25 '12 at 10:55
@Iuli Since $\mathrm{LHS}(x, y, z) = \mathrm{LHS}(kx, ky, kz)$, if the inequality holds for $(x, y, z)$, it holds for each $(kx, ky, kz)$ with $k > 0$. So, for example, if you want to prove the inequality for $(x, y, z)$, it is sufficient you prove it for $(kx, ky, kz)$ with $k = 1/\sqrt{x^2 + y^2 + z^2}$ and that is equivalent to assume the condition $x^2 + y^2 + z^2 = 1$. Of course, you are free to choose other values for $k$ and therefore other conditions on $(x, y, z)$. $k = 1/\sqrt[3]{abc}$, for example, is equivalent to the condition $abc=1$. (continue) – AlbertH Sep 25 '12 at 12:01
@Iuli I used the condition $x^2 + y^2 + z^2 = 1$ because I felt it would have simplified the structure of the inequality and (overall) reduced the amount of symbols to write. However, the line of the proof remains the same also without the above assumption. – AlbertH Sep 25 '12 at 12:01
There are a number of proofs for that inequality (with explanations) at – Andreas Mar 24 at 12:13

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.